2022
DOI: 10.1007/s11920-022-01398-1
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Physicians in the Workplace: Trends, Causes, Consequences, and Strategies for Intervention

Abstract: Purpose Violence against healthcare professionals has become an emergency in many countries. Literature in this area has mainly focused on nurses while there are less studies on physicians, whose alterations in mental health and burnout have been linked to higher rates of medical errors and poorer quality of care. We summarized peer-reviewed literature and examined the epidemiology, main causes, consequences, and areas of intervention associated with workplace violence perpetrated against physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 100 publications
1
39
0
10
Order By: Relevance
“…Policies and legislation targeting violent acts against the healthcare team should be developed and activated. Caruso et al suggested the implementation of a two-level interventional system [ 51 ]. At the intra-institutional level, strategies should be developed to reduce institutional causes of violence (e.g., providing comfortable conditions to mitigate long waiting times precipitated by overcrowding).…”
Section: Discussionmentioning
confidence: 99%
“…Policies and legislation targeting violent acts against the healthcare team should be developed and activated. Caruso et al suggested the implementation of a two-level interventional system [ 51 ]. At the intra-institutional level, strategies should be developed to reduce institutional causes of violence (e.g., providing comfortable conditions to mitigate long waiting times precipitated by overcrowding).…”
Section: Discussionmentioning
confidence: 99%
“…Workplace violence directed toward healthcare providers encompasses all “incidents where staff are abused, threatened or assaulted in circumstances related to their work […], involving an explicit or implicit challenge to their safety, well-being or health” [ 1 , 2 ]. It is an important concern that has been exacerbated by the COVID-19 pandemic [ 2 , 3 , 4 , 5 , 6 , 7 ]. Recent systematic reviews and meta-analyses show that between 57–67% of the workforce experiences verbal abuse and 21–33% experiences threats of physical violence [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence, at its worst, results in fatalities such as in the case of an orthopedic surgeon in Tulsa, Oklahoma, who was killed in a mass shooting by a disgruntled former patient [ 10 ]. Non-fatal violence incidents have personal and occupational consequences such as emotional distress, poor health behaviors, psychiatric disorders, and diminished job satisfaction/performance [ 3 ]. Despite the high prevalence of healthcare workplace violence, there are aspects of the problem that remain unaddressed and understudied [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations